PENGENALAN DAN PEMANFAATAN INTERNET OF THINGS (IOT) PADA SANTRI DAN SANTRIWATI PESANTREN NAFIDATUNNAJAH - Herwis Gultom; Chandra Alim; Ahmad Fauzi (Abdi Jurnal Publikasi, 2024)
Improving the quality of education in Indonesia is done in various ways. One way is to change conventional education into technology-based education. The strategy for improving the quality of education is carried out by implementing information technology in learning at school. The strategy for improving the quality of education is carried out by implementing information technology in learning at school. The development of Information and Communication Technology (ICT) continues to progress so rapidly. Continuous technological progress continues throughout human history, this has shown that there is a process of change and development in digital technology innovation. Based on the description above, the use of digitalization to improve the quality of learning and supporting facilities can be a solution to provide new knowledge in the teaching and learning process. Due to the description above, the aim of this service is to introduce the Internet of Thinks to Islamic boarding school students to increase knowledge and improve the quality of daily learning